Discrepancies and Research Gaps on the Lithostratigraphy of the Jajarkot Thrust Sheet, Western Nepal Himalaya - Lamsal, Sunil; Shah, Ram Bahadur; Paudyal, Kabi Raj (Journal of Institute of Science and Technology, 2023)
The interaction between the Indian and Asian plates has led to the formation of imbricated thrust sheets in the Himalayas. This study focuses on a segment of the Jajarkot Thrust Sheet, characterized by metamorphic rocks, including garnet-biotite schist, biotite schist, quartzite interlayers, and marbles. The upper stratigraphic sequence of this thrust sheet contains fossiliferous rocks from the Paleozoic era. Prior classifications have identified three main units: Chaurjhari Formation, Thabang Formation, and Jaljala Formation. However, the Department of Mines and Geology recognizes two units: Siuri Formation and Surbang Formation. This discrepancy, along with inconsistent terminologies like "Jajarkot nappe" and "Jajarkot klippe", highlights the need for a unified stratigraphic framework. Such clarity is crucial for assessing mineralization potentials, particularly for iron and copper, in western Nepal and understanding the thrust sheet's tectonic history within the broader Himalayan context.